Unifying NAPL Drawdown and Transmissivity Testing in Unconfined, Confined, Perched, and Fractured Settings using the Z‐Factor and MH Principles - Kirkman, Andrew J.; Koons, Brad (Ground water monitoring & remediation, 2020)
Light nonaqueous phase liquid (LNAPL) flow in in fractured rock is governed by the same physics as porous media, but LNAPL discharge to a well from fractured rock is subject to the unique geometry of the fractures within the rock and the degree of interconnectivity between the factures. Previous conceptualization and definition of drawdown of nonaqueous phase liquids (NAPL) has employed a single drawdown value to represent the entire vertical interval of mobile NAPL. Application of the single drawdown model may result in erroneous calculation of NAPL transmissivity in fractured rock settings. This work illustrates how drawdown in multiphase systems can be variable over the vertical interval of mobile NAPL. In settings with discrete fracture networks, it is clear that consistently applying a single drawdown value will not accurately represent the pressure gradients. This work presents the multiphase head (MH) model, which is proposed as a comprehensive methodology for evaluating NAPL drawdown in fractured rock, and unconsolidated porous media. The MH model utilizes fluid statics and physical principles to accurately represent pressure differences in the formation and convert those into NAPL drawdown for discrete elevations. This first principles approach to describing how drawdown varies with NAPL‐production zone elevations and fluid levels, resulting in a more accurate representation of discharge vs. fluid elevation behavior. Application of the MH model to various scenarios has identified that dissimilar scenarios can represent similar behavior during recovery from a NAPL removal event or baildown test. The resulting understanding improves the selection of representative portions of baildown test data to use in NAPL transmissivity analysis. Proper conceptualization of drawdown in bedrock identifies an alternate analysis method, the Z‐factor, to estimate NAPL transmissivity. The resulting drawdown calculations and transmissivity analysis method result in a comprehensive approach to calculating NAPL transmissivity in both bedrock and unconsolidated porous media.